Complex index of refraction of indium nitride InN - Akinlami, J.O.; Bolaji, F.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
We have investigated the complex index of refraction of Indium Nitride (InN). We obtained refractive index which has the maximum value 2.59 at the photon energy 5.30 eV, the extinction coefficient which has the maximum value 0.86 at the photon energy 5.30 eV, the dielectric constant, the real part of the complex dielectric constant with the peak value 5.90 at the photon energy 5.30 eV and the imaginary part of the complex dielectric constant with the maximum value 4.48 at the photon energy 5.30 eV, the transmittance with the maximum value 0.1402 at the photon energy 5.3 0eV, the absorption coefficient which has its maximum value 86.0 at the photon energy 11.50 eV and reflection coefficient which with the maximum value 0.49 at the photon energy 5.3 eV. Thus, InN has the potential to operate optimally in a photonic device at the photon energy 5.30 eV.